2003
DOI: 10.3201/eid0912.030230
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin Treatment Failure in Typhoid Fever Case, Pakistan

Abstract: We report a case of ciprofloxacin treatment failure in a typhoid fever patient at a tertiary care hospital in Rawalpindi, Pakistan. This case shows not only the emergence of fluoroquinolone resistance in typhoid salmonellae but also the inadequacy of the current laboratory guidelines for detection of this resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…Sporadic cases of ciprofloxacin treatment failure in typhoid fever have been reported in Europe and, more recently, in Asia [31,12]. The increase of MDR S. Typhi has been attributed to the misuse of drugs, not only in the treatment of typhoid, but also in the treatment of other diseases that may be caused by other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic cases of ciprofloxacin treatment failure in typhoid fever have been reported in Europe and, more recently, in Asia [31,12]. The increase of MDR S. Typhi has been attributed to the misuse of drugs, not only in the treatment of typhoid, but also in the treatment of other diseases that may be caused by other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal detection of endemic strains with reduced susceptibility to fluoroquinolones, for example, ciprofloxacin MIC ≥ 0.125 or ofloxacin [6], is crucial as this drug is frequently used by family physicians for the management of typhoid. Emergence of strains with reduced susceptibility to fluoroquinolone has led to treatment failure, as previously reported in regional and local studies [7,8)]. The method of screening with nalidixic acid has been validated and reported to be efficient for endogenous isolates and is currently in use by many laboratories in Pakistan [9,10].…”
Section: Introductionmentioning
confidence: 85%
“…However, a single isolate of Salmonella Typhi and two of Salmonella Paratyphi A were found to be resistant towards Ceftriazone. Increasing rates of resistance to quinolones and decreased susceptibility to fl uoroquinolones, reported in a study 18 might make us consider Chloramphenicol as an alternative drug for the treatment of resistant strains of Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…17 In recent years many case studies has shown failure in the treatment of enteric fever with isolates susceptible to fl uoroquinolones and resistant to Nalidixic acid. 2,18 Hence routine testing of resistance to Nalidixic acid can serve as a useful screening test for fl uoroquinolones. 18 The increase in the resistivity of the antibiotics like Ciprofl oxacin from 0 % in 2005 to 33.33 % in 2013 might have occurred due to the long-term use of the drugs or the misuse of the drugs by the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation